2015
DOI: 10.1590/1806-9282.61.02.126
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients with rheumatoid arthritis under biological therapy

Abstract: Conflict of interest: noneObjective: assessing health-related quality of life (HRQL) in patients with rheumatoid arthritis (RA), before and after treatment with biological therapy. Methods: a longitudinal study, conducted from November 2010 to September 2011, with implementation of the instruments HAQ II (health assessment questionnaire) and SF-36 (medical outcomes short-from health survey). Barlett test, Anova, Friedman and paired t-test were performed for multiple extracts.Results: 30 patients were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
2
9
0
2
Order By: Relevance
“…Our results indicate that females were more affected by RA than males. These results are similar to those from other studies that demonstrated that women are more likely to develop RA than men and it is two to three times more prevalent in women than in men [ 2 , 10 ]. Most of RA patients in our study were aged between 36 and 50 years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results indicate that females were more affected by RA than males. These results are similar to those from other studies that demonstrated that women are more likely to develop RA than men and it is two to three times more prevalent in women than in men [ 2 , 10 ]. Most of RA patients in our study were aged between 36 and 50 years.…”
Section: Discussionsupporting
confidence: 91%
“…Most of RA patients in our study were aged between 36 and 50 years. A study conducted in a Dutch nationwide group of 1056 patients showed that the onset of RA reaches a peak between the ages of 40 and 50 years [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22][23][24] The lower number of points in the PCS domain in comparison to the MCS domain may indicate that RA affects more the physical than the mental sphere as indicated by other authors. 21,23,24 It was also shown that the quality of life of patients with RA depends on many factors of physical, mental and social functioning sphere.…”
Section: Discussionmentioning
confidence: 99%
“…21,23,24 It was also shown that the quality of life of patients with RA depends on many factors of physical, mental and social functioning sphere. 17,[19][20][21][23][24][25][26][27][28][29][30][31] Studies conducted by many authors have shown that poorer functioning of the respondents in the physical sphere is conditioned by the duration of the disease. 18,24,26,28,30 Studies by Baloglu et al and Wisłowska et al did not confirm this dependence.…”
Section: Discussionmentioning
confidence: 99%